If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n = 3(n + -2) Reorder the terms: 9n = 3(-2 + n) 9n = (-2 * 3 + n * 3) 9n = (-6 + 3n) Solving 9n = -6 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 9n + -3n = -6 + 3n + -3n Combine like terms: 9n + -3n = 6n 6n = -6 + 3n + -3n Combine like terms: 3n + -3n = 0 6n = -6 + 0 6n = -6 Divide each side by '6'. n = -1 Simplifying n = -1
| 3x^2-12+165=180 | | 1-4x+4x^2=0 | | 2(3y-1)=-4 | | f=1.8x-11+32 | | F(9)=8 | | 3=3+-0.6 | | u^2-19u+90=0 | | X+30+63=180 | | 9a-25= | | 3x+15=2x-9 | | 5(b-4)=5b-2 | | 7y-4=7y+6 | | 0=3+-0.6 | | 28-x=-6(x-5)+5x | | 24=-8k-6k | | w+4W+12=13W+9 | | 6x-17x-28=0 | | 4c^2-1= | | 3b+7=2b-4 | | -3=3+-0.6 | | 2x+7+7=-3(x-3)+3(1+2x) | | 5/2d-3=10/d+3 | | 5g-4+g+16=2(3g-8) | | (5x-42)=x | | 50+15x=50 | | 5[-3(4x+3)+5(3x-2)]= | | 1000=(30+x)(15+x) | | 14-2x+4x=72 | | 10=-5(x-5) | | 2r-(5+-r)=13+2r | | 3x-(x+1)=-2+5(x-4) | | 0.9x=.2 |